Folded-optics-based quartz-enhanced photoacoustic and photothermal hybrid spectroscopy - Ruyue Cui; Hongpeng Wu; Frank K. Tittel; Vincenzo Spagnolo; Weidong Chen; Lei Dong (Photoacoustics, 2024)
Folded-optics-based quartz-enhanced photoacoustic and photothermal hybrid spectroscopy (FO-QEPA-PTS) is reported for the first time. In FO-QEPA-PTS, the detection of the photoacoustic and photothermal hybrid signal is achieved through the use of a custom quartz tuning fork (QTF), thereby mitigating the issue of resonant frequency mismatch typically encountered in quartz-enhanced photoacoustic-photothermal spectroscopy employing multiple QTFs. A multi-laser beam, created by a multi-pass cell (MPC) with a designed single-line spot pattern, partially strikes the inner edge of the QTF and partially passes through the prong of the QTF, thereby generating photoacoustic and photothermal hybrid signals. To assess the performance of FO-QEPA-PTS, 1 % acetylene is selected as the analyte gas and the 2f signals produced by the photoacoustic, the photothermal, and their hybrid effects are measured. Comparative analysis against QEPAS and QEPTS reveals signal gain factors of ∼ 79 and ∼ 14, respectively, when these laser beams created by MPC excite the QTF operating at fundamental resonance mode in phase. In the FO-QEPA-PTS signal, the proportions of the photoacoustic and the photothermal effects induced by the multiple beams are ∼7 % and 93 %, respectively.